Public Service Delivery in Remote Villages: An Assessment Using the SERVQUAL Model in Allang, Maluku - Huwae, Grisela; Renyut, Bernard C; Setitit, Ignasius (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
This study aims to evaluate the quality of public services in Allang Village, Leihitu Barat Subdistrict, Central Maluku Regency using a qualitative approach based on the SERVQUAL model. The background of this research stems from the fact that public services at the village level, particularly in archipelagic regions such as Maluku, still face various challenges including limited infrastructure, low work discipline among village officials, and suboptimal digitalization of services. Data were collected through semi-structured interviews, field observations, and document analysis involving 8 village officials and 41 community service users. The results indicate that, in general, public service delivery in Allang Village falls into the category of fairly good. The dimensions of responsiveness and empathy are the most prominent, as reflected in the responsive, friendly attitudes and social concern of the village officials towards the community. Meanwhile, the tangible and reliability dimensions still require improvement, particularly regarding the adequacy of service facilities and the consistency of staff attendance. These findings highlight the importance of strengthening the capacity of village officials, improving infrastructure, and implementing technology-based service systems to enhance accountability and efficiency. This study is expected to serve as a reference in formulating village public service policies that are more professional, participatory, and sustainable.